DETERMINAN PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (Studi Empiris pada WPOP yang terdaftar di KPP Pratama Malang Utara) - Eva Wulandari; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this study was to determine the Effects of Discrimination, Justice, Taxation Systems, Tax Rates, and the Possibility of Fraud Detection of Taxpayers' Perceptions regarding the Ethics of Tax Evasion. The population in this study are taxpayers registered in North Malang KPP. Sampling using Slovin formula. Data was collected using a questionnaire method distributed to respondents and processed using SPSS Statistics 23. The results of this study indicate that discrimination, the taxation system, and the possibility of fraud detected have a significant positive effect on perceptions of taxpayers regarding the ethics of tax evasion, while justice and tax rates do not have significant influence on taxpayers' perceptions regarding the ethics of tax evasion.Keyword          : Discrimination, Justice, Taxation System, Tax Rates, Fraud